Methodological strategies applied in the esnglish languaje teaching - learning process to develop the writing skill in the first - year student of baccalaureate at José Miguel García Moreno anda José María Velasco Ibarra educational units, in the city of El Guabo, during the academic period 2013 - 2014. - Flores Granda, Clara Jacqueline; Vivas Barrios, Viviana Raquel (Machala : Universidad Técnica de Machala, 2015)
Este trabajo de investigación fue llevado a cabo en la ciudad de El Guabo, provincia de El Oro, en las Unidades Educativas José Miguel García Moreno y José María Velasco Ibarra para determinar el nivel de aplicación de estrategias metodológicas en el proceso de enseñanza y aprendizaje del idioma ingles para desarrollar la escritura en los estudiantes de primer año de bachillerato, djurante el período académico 2013-2014: con el fin de diseñar y llevar a cabo un taller para incrementar los conocimientos de los maestros de Inglés acerca de estrategias metodológicas actualizadas para desarrollar la escritura.
This research was conducted in the city of El Guabo province of El Oro, in the Educational Units José Miguel García Moreno and Jose Maria Velasco Ibarra to determine the level of implementation of methodological strategies in the process of teaching and learning English language for developing writing students in first year of high school, djurante academic period 2013-2014: In order to design and conduct a workshop to enhance the skills of English teachers about teaching strategies to develop updated writing.
Keywords: METHODOLOGICAL; STTRATEGY; LEARNING